Antifungal Effects of Volatile Organic Compounds Produced by Rahnella aquatilis JZ-GX1 Against Colletotrichum gloeosporioides in Liriodendron chinense × tulipifera - Kong, Wei-Liang; Rui, Lin; Ni, Hang; Wu, Xiao-Qin (Frontiers in Microbiology, 2020)
The use of volatile organic compounds (VOCs) produced by microorganisms for the biological control of plant diseases has attracted much attention in recent years. In this study, the antifungal activity and identity of VOCs produced by Rahnella aquatilis JZ-GX1 isolated from the rhizosphere soil of pine were determined and analysed. The effect of the VOCs on the mycelial growth of Colletotrichum gloeosporioides, the pathogen of Liriodendron chinense × tulipifera black spot, was determined by a joined-petri dish fumigation method. An in vitro leaf inoculation method was used to determine the fumigation effect of the VOCs on Liriodendron black spot. VOCs with antifungal activity were collected by headspace solid-phase microextraction (SPME), and their components were analysed by gas chromatography-mass spectrometry (GC-MS). The results showed that the VOCs secreted by JZ-GX1 inhibited the mycelial growth of the tested pathogen. The VOCs destroyed the morphology of the mycelium, significantly increased the permeability of the cell membrane and downregulated the expression of pathogenicity-related genes during mycelial infection, thus inhibiting the expansion of anthracnose disease spots in leaves. In the volatile compound profile, 3-methyl-1-butanol and 2-phenylethyl methyl ether significantly inhibited the mycelial growth and spore germination of C. gloeosporioides. This work provides a new strategy for the research and application of microorganisms and bioactive compounds to control plant anthracnose.